Comparing Efficacy and Safety of Piperacillin/tazobactam and Amoxicillin/clavulanic acid in the Treatment of Complicated Urinary Tract Infections - Sara Abolghasemi; Mehrandokht Mardani; Shahnaz Sali; Iman Ghasemzadeh (Novelty in Biomedicine, 2022)
Background: There has been an increasing concern regarding high morbidity and mortality rate among patients with severe and complicated urinary tract infections (UTIs) and their related complications. Hence, there is a great demand for choosing the best treatment protocol. In the study, we evaluated and compared the efficacy of piperacillin/tazobactam and amoxicillin/clavulanic acid for treating complicated urinary tract infections. Materials and Methods: This study enrolled 42 patients suffering from UTIs referred to Labbafinezhad hospital, Tehran, Iran. Subjects were randomly assigned to receive intravenous piperacillin/tazobactam or intravenous amoxicillin/clavulanic acid. Clinical manifestations, vital signs, laboratory parameters, and drug side effects within three days of completing the treatment protocols were evaluated and compared between the two groups. Data analysis was performed using SPSS version 16.0. A P-value of less than 0.05 was considered significant. Results: There was no significant difference in the frequency of pyuria and hematuria between the two groups before and after the intervention. The frequency of positive urine cultures for extended-spectrum beta-lactamase bacteria, Escherichia coli, was also similar between patient groups before intervention. However, a statistically significant difference in the rate of positive urine cultures for Klebsiella was found between the two groups. There was no significant difference between the two groups in terms of clinical signs and symptoms, including fever, dysuria, frequency, pain intensity, supra-pubic pain, or nausea and vomiting before the intervention, as well as within 72 hours after treatment. The vital signs were also similar between these two groups. No drug side effect was found among patients. Conclusion: Blocking the function of orexin-A in the lactating rats decreased the expression of lipogenic mammary enzymes and serum insulin. Conclusion: Using piperacillin/tazobactam or intravenous amoxicillin/clavulanic acid was effective and safe for treating complicated UTIs. Clinicians should consider the cost and availability of these drugs to choose the most appropriate treatment for the patients.